Challenges Affecting the Adjudication of Islamic Finance Cases in the Malaysian Courts - Md Nor, Mohd Zakhiri; Md Dahlan, Nuarrual Hilal; Azhar, Alias; Mohd Khalid, Al Hanisham; Mohamad, Ani Munirah (American Scientific Publishers, 2017)
The Islamic banking and finance industry in Malaysia is developing progressively, primarily due to the concerted effort from the regulators and the industry players alike. The Islamic funds are increasing over the years and more innovative products are introduced for the benefit of the consumers. In some situations, disputes arise relating to the Islamic finance matters, and they end up for the adjudication of the courts system. However, there have been debates as to the challenges affecting the adjudication of such cases in the Malaysian courts. Engaging in library-based research, this paper outlines the various challenges affecting the adjudication of Islamic finance cases in the Malaysian courts, involving both legal and operational aspects of the implementation of Islamic finance business in the nation. The challenges include the legal infrastructure puts Islamic finance cases within the jurisdiction of the conventional legal framework, Islam is separated from the administration of justice, different roles played by different components of Islamic finance, separate laws govern the different components of Islamic finance, confusion caused by the building blocks of the legal documentation and the question as to the competency of civil court judges. Accordingly, the future direction of the research is to propose recommendations for the management or dissolution of these challenges, towards better settlement of the Islamic finance cases by the courts.